(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This research aims to determine the effect of differentiated learning and learning styles on student learning outcomes in the material of physical changes and chemical changes. This type of research is a quasi-experiment with a 2x3 factorial design. The research population was all seventh grade students at Gonzaga Tomohon Catholic Middle School for the 2023/2024 academic year, totaling 151 people. The research sample was classes 7b and 7c, each consisting of 29 people. Hypothesis testing was carried out with the SPSS 22.0 for Windows program using two way Anova analysis. The results of the research show that (1) there is no significant influence of learning style on student learning outcomes in the material of physical changes and chemical changes (2) there is a significant influence of the application of differentiated learning on student learning outcomes in the material of physical changes and chemical changes (3) there is no There is a significant influence of the interaction between learning styles and differentiated learning on student learning outcomes in physical changes and chemical changes. The average learning outcomes of students taught with differentiated learning are higher than those of students taught with conventional learning. In differentiated learning, the average learning outcomes of students who have an auditory learning style are higher than students who have a visual and kinesthetic learning style. In conventional learning, the average learning outcomes of students who have a visual learning style are higher than students who have an auditory and kinesthetic learning style.